Adverse events reported to the U.S. Food and Drug Administration Adverse Event Reporting System for tisagenlecleucel. Issue 9 (11th June 2021) - Dores, Graça M.; Jason, Christopher; Niu, Manette T.; Perez‐Vilar, Silvia
Abstract: The U.S. Food and Drug Administration (FDA) approved the first chimeric antigen receptor T‐cell therapy, tisagenlecleucel, in August 2017. We sought to describe adverse events (AEs) reported to the FDA Adverse Event Reporting System (FAERS) for tisagenlecleucel in the post‐marketing period. We searched FAERS reports to identify U.S. patients treated with tisagenlecleucel between August 30, 2017‐August 31, 2019. We reviewed individual reports, calculated AE frequencies and reporting rates (RRs), and used Empirical Bayesian Geometric Mean methods to identify disproportionate reporting. We identified 646 de‐duplicated reports with a median age at AE of 18 (interquartile range: 11–56) years. The overall RR was 81.0%, and more than 95% of reports described a serious outcome. Cytokine release syndrome (CRS) was the most frequently reported AE (51.1%) with a RR of 41.4%; neurotoxicity was reported less frequently (21.2%), with a RR of 17.2%. Most disproportionately reported AEs were listed on the package insert or confounded by indication. We identified 13 subsequent neoplasms (SPN), the majority occurring within 6 months of tisagenlecleucel administration, and none reporting evidence of insertional mutagenesis. A total of 165 reports (26%) described a death outcome; most deaths occurred >30 days after treatment. The majority of deaths (64%) were due to progression of the underlying lymphoid neoplasm, and few (<5%) were attributed to CRS or neurotoxicity. We did not identify new safety concerns reported for tisagenlecleucel in the post‐marketing period. Reporting rates for CRS and neurotoxicity were lower than identified in the prelicensure clinical trials.